The trypanocidal benznidazole promotes adaptive response to oxidative injury: involvement of the nuclear factor-erythroid 2-related factor-2 (Nrf2) and multidrug resistance associated protein 2 (MRP2) - Rigalli, Juan Pablo (Toxicology and applied pharmacology, 2016)
Oxidative stress is a frequent cause underlying drug-induced hepatotoxicity. Benznidazole (BZL) is the only trypanocidal agent available for treatment of Chagas disease in endemic areas. Its use is associated with side effects, including increases in biomarkers of hepatotoxicity. However, BZL potential to cause oxidative stress has been poorly investigated. Here, we evaluated the effect of a pharmacologically relevant BZL concentration (200μM) at different time points on redox status and the counteracting mechanisms in the human hepatic cell line HepG2. BZL increased reactive oxygen species (ROS) after 1 and 3h of exposure, returning to normality at 24h. Additionally, BZL increased glutathione peroxidase activity at 12h and the oxidized glutathione/total glutathione (GSSG/GSSG+GSH) ratio that reached a peak at 24h. Thus, an enhanced detoxification of peroxide and GSSG formation could account for ROS normalization. GSSG/GSSG+GSH returned to control values at 48h. Expression of the multidrug resistance-associated protein 2 (MRP2) and GSSG efflux via MRP2 were induced by BZL at 24 and 48h, explaining normalization of GSSG/GSSG+GSH. BZL activated the nuclear erythroid 2-related factor 2 (Nrf2), already shown to modulate MRP2 expression in response to oxidative stress. Nrf2 participation was confirmed using Nrf2-knockout mice in which MRP2 mRNA expression was not affected by BZL. In summary, we demonstrated a ROS increase by BZL in HepG2 cells and a glutathione peroxidase- and MRP2 driven counteracting mechanism, being Nrf2 a key modulator of this response. Our results could explain hepatic alterations associated with BZL therapy.
Gesehen am 21.10.2021